Randomised controlled trial to evaluate the effectiveness of using the RD-1-based C-Tb skin test as a replacement for blood-based interferon-γ release assay for detection of, and initiation of preventive treatment for, tuberculosis infection: RID-TB:Dx study protocol. Issue 12 (30th December 2021) - Rangaka, Molebogeng X; Hamada, Yohhei; Duong, Trinh; Bern, Henry; Calvert, Joanna; Francis, Marie; Clarke, Amy Louise; Ghanouni, Alex; Hack, Vanessa; Owen-Powell, Ellen; Surey, Julian; Sanders, Karen; et al.
Abstract : Introduction: The predictive utility for incident tuberculosis (TB) of the purified protein derivative tuberculin skin test and region of difference 1 (RD1)-based interferon-gamma release assays (IGRA) is comparable; and either is recommended to test for latent TB infection (LTBI). Despite associated high costs of IGRA, sites participating in LTBI screening in many high-income settings pragmatically favour IGRA due to its higher specificity and simpler logistics. A new RD1-based skin test, C-Tb, could offer an acceptable and as accurate, cheaper alternative to IGRA. Evaluating the impact of C-Tb on process and patient-related outcomes would provide important information to help guide its use in LTBI testing strategies. Methods and analysis: This is a pragmatic multicentre, open-label, non-inferiority, randomised controlled trial. The trial will assess the initiation of LTBI treatment following a positive result of the randomised test as the primary outcome. Participants will be randomised to receive the C-Tb test (intervention) or IGRA (usual care, control) for initiation of treatment. We will enrol 1530 participants in England aged≥16 years who are eligible for LTBI testing and treatment according to UK guidance. In the C-Tb arm, skin induration will be assessed 2–3 days after intradermal injection and measured in millimetres of induration. Results of IGRA will be obtained in line with standard practice. Behavioural studies will explore people's experiences, perspectives and preferences of LTBI testing and treatment. Economic analysis will estimate cost-effectiveness of changes to the diagnostic algorithm for LTBI. The protocol was developed with Patient and Public Involvement (PPI), which will continue throughout the trial. Ethics and dissemination: Ethics approval has been obtained from The NHS Health Research Authority (269485). We will share results of the trial in peer-reviewed journals and conferences. Trial registration number: EudraCT 2019-002592-34; ISRCTN17936038 .